The Influence of Wordwall-Based Interactive Learning Media on Students' Learning Motivation in Mathematics Subjects for Grade III Elementary School - Juraidah, Juraidah; Diana, Nanang; Akbar, Purnama Raya (FKIP - Universitas Riau, 2025)
This study aims to examine the effectiveness of the Wordwall application in enhancing students' learning motivation of grade 3 students of SDN Inpres Sakuru. The problems found were the lack of motivation to learning mathematics such as not focusing on learning, lack of self-confidence and the use of media that had not been implemented properly. This study used a quantitative approach with a One Group Pretest Posttest design to see motivation before and after treatment. The sample in this study was 27 students. To measure motivation, data were obtained from respondents' answers on the questionnaire statement sheet. Before being given treatment, the initial motivation was 28.37 then after being given treatment it increased by 44.88. This shows an increase in the motivation of grade 3 students. Based on statistical analysis, a significance value of 0.000 was obtained which means it is smaller than the significance level of 0.05, thus it can be concluded that Ha is accepted and H0 is rejected. This finding shows that there is a difference in students' learning motivation scores before and after treatment. This means that the use of interactive learning media assisted by Wordwall has a significant effect on increasing students' learning motivation.